PENGARUH UKURAN PERUSAHAAN, PERGANTIAN AUDIT, AUDIT TENURE, DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY: (Studi Empiris pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Andri Andri; Anisa Anisa (Pusat Riset dan Inovasi Nasional, 2024)
The more rapidly the capital market in Indonesia develops, the more go public companies are listed, to keep up with existing competitiveness, companies listed on going public must issue financial reports. Financial reports are one of the most important instruments in seeing the performance of a company, especially companies that go public. This study looks at the effect of company size, audit turnover, audit tenure delay, and financial distress on audit delay in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during 2017-2021. The type of research used is quantitative research, by taking samples using the purposive sampling method, namely 100 observation data. The analysis technique uses descriptive statistical tests, logistic regression models, then calculated using Microsoft Excel and processed with Eviews 12. The results of this study are company size, audit turnover, audit tenure, and financial distress simultaneously influence audit delay. Audit turnover has a partial effect, because the new audit takes longer to adjust to understanding the characteristics and scope of the company. Financial distress has a partial effect on audit delay, companies that experience unfavorable finances, companies will focus on improving audit planning, will also have an impact on the auditing process. Meanwhile, company size has no effect on audit delay, even though the larger the assets owned by the company, the company will still complete financial reports on time, and tenure audits have no partial effect on audit delay, because auditors are rules that have been regulated, so it will not have an impact on completion and preparation of audited financial reports.